Sewerage and Water Supply Draft Sixth Five Year Plan (1978-83) Government of Manipur - Planning Commission (Planning Commission, 1978)
The State was having a scheme of 1 lakh galIons per day capacity which continued until the installation of the present 3.2 mgd. Plant. This augmentation scheme was taken during the 3rd Plan. The 1st Phase of 1.6 mgd. was commissioned in 1965 and 2nd Phase of 1.6 mgd. was coming signed in 1973.
Government of Manipur, Public Health Engineering Organisation